Altmetrics: Six Years of Changing Scholarly Appraisal - Samanta, Dyuti; Dutta, Bidyarthi (Journal of Information and Knowledge, 2017)
The last decade of the 20th century was marked as the opening gateway to internet and communication revolution, which added new dimensions to information and knowledge society. The scholarly community of today’s knowledge society communicates between each other in a non-traditional way besides the traditional way. The arrival of web 2.0 and scientists’ gradual use of said platforms as tools for the diffusion and receipt of scientific information and with part of the scientific community relatively receptive, that scientometrics 2.0 began to be discussed. Another milestone in the era of scientometrics 2.0 is the ‘Wikimetrics’. After the ‘Wikimetrics’ next footprint comes with the advent of ‘Article-level metrics’. Article-level metrics followed by Altmetrics, i.e. Alternative Metrics. The term altmetrics was coined by Jason Priem in 2010, as a generalization of article level metrics, and rooted in the twitter #altmetrics hashtag. Although altmetrics usually functions as metrics about articles, but it can also be applied to people, journals, books, data sets, presentations, videos, source code repositories, web pages, etc. Altmetrics does not cover just citation counts, but also other aspects of the impact of a work, such as how many data and knowledge bases refer to it, article views, download, or mentions in social media and news media. In this paper, the altmetric scores of top-cited altmetric papers are presented. Also, the contents of the same are analysed and presented. It is interesting to note that all top-cited papers appeared from diverse subject domains, i.e. big data in science, biological science, medical science, research methodology, social studies, citation studies and scientometrics, different issues involved in social networking et al. The subject domain altmetrics is a highly interdisciplinary field covering all major areas of universe of knowledge. This study reflects other notable feature, i.e. the discord between traditional metric (times cited) and modern metric (altmetric score).